The persistence of mineral-associated organic matter varies with time and litter quality - Preeti Singh; Saliha Irshad; Ondřej Mudrák; Gerrit Angst; Martin Bartuška; Jan Frouz (Soil Biology and Biochemistry, 2026)

Earthworms promote soil organic carbon formation across management histories without stimulating the mineralization of native carbon - Janus den Toonder; Šárka Angst; Jan Frouz; Veronika Jílková; Jaroslav Kukla; Travis B. Meador; Stefan Scheu; Karel Tajovský; Gerrit Angst (Biology and Fertility of Soils, 2026)

Soil mesofauna promote mineral-associated organic matter formation under ambient and future climates - Gerrit Angst; Lisa Hinkelthein; Qun Liu; Alfred Lochner; Ondřej Mudrák; Travis Meador; Martin Schädler; Stefan Scheu; Marie Sünnemann; Rui Yin; Šárka Angst; Nico Eisenhauer (Agriculture, Ecosystems & Environment, 2026)

Rapid allocation of freshly added organic nitrogen to particulate organic matter in ectomycorrhiza- but not arbuscular mycorrhiza-dominated forests - Andrey G. Zuev; Amelie Hauer; Gerrit Angst; Antonis Chatzinotas; Nico Eisenhauer; Olga Ferlian; Stephanie D. Jurburg; Epp Maria Lillipuu; Maarja Öpik; Martti Vasar; Ajuan Zhang; Anna I. Zueva; et al. (Soil Biology and Biochemistry, 2026)

Mycorrhizal allies: synergizing forest carbon and multifunctional restoration - Tengteng Li; Richard P. Phillips; Matthias C. Rillig; Gerrit Angst; E. Toby Kiers; Paola Bonfante; Nico Eisenhauer; Zhanfeng Liu (Trends in Ecology & Evolution, 2025)

Marcescence in temperate regions mediates tree litter decomposition through abiotic factors - Šárka Angst; Ondřej Mudrák; Martin Bartuška; Kateřina Čápová; Veronika Jílková; Petr Petřík; Gerrit Angst (Soil Biology and Biochemistry, 2025)

The role of death and lysis of microbial and plant cells in the formation of soil organic matter - Paolo Nannipieri; Gerrit Angst; Carsten Mueller; Giacomo Pietramellara (Soil Biology and Biochemistry, 2025)

Soil organic matter persistence in hyperhumic colluvial soils caused by palaeofires, root inputs and mineral binding - Joeri Kaal; Antonio Martínez Cortizas; Gerrit Angst; Cynthia Kallenbach; Cruz Ferro Vázquez; Felipe Criado-Boado (Organic Geochemistry, 2024)

Stabilized microbial necromass in soil is more strongly coupled with microbial diversity than the bioavailability of plant inputs - Gerrit Angst; Šárka Angst; Jan Frouz; Stanislav Jabinski; Veronika Jílková; Jaroslav Kukla; Mengmeng Li; Travis B. Meador; Roey Angel (Soil Biology and Biochemistry, 2024)

Earthworms facilitate stabilization of both more-available maize biomass and more-recalcitrant maize biochar on mineral particles in an agricultural soil - Anna Kellerová; Gerrit Angst; Veronika Jílková (Soil Biology and Biochemistry, 2024)

Macrofauna amplify plant litter decomposition and stabilization in arctic soils in a warming climate - Veronika Jílková; Petr Macek; Gerrit Angst; Martin Bartuška; Josef Starý; Vladimír Šustr; Miloslav Devetter (Soil Biology and Biochemistry, 2024)

Root but not shoot litter fostered the formation of mineral-associated organic matter in eroded arable soils - Eva Kaštovská; Michal Choma; Gerrit Angst; Rainer Remus; Jürgen Augustin; Steffen Kolb; Stephan Wirth (Soil and Tillage Research, 2024)

Climate-dependent plant responses to earthworms in two land-use types - Qun Liu; Nico Eisenhauer; Stefan Scheu; Gerrit Angst; Miriam Bücker; Yuanyuan Huang; Travis B. Meador; Martin Schädler (Oecologia, 2024)
Plant nutrient uptake and productivity are driven by a multitude of factors that have been modified by human activities, like climate change and the activity of decomposers. However, interactive effects of climate change and key decomposer groups like earthworms have rarely been studied. In a field microcosm experiment, we investigated the effects of a mean future climate scenario with warming (+ 0.50 °C to + 0.62 °C) and altered precipitation (+ 10% in spring and autumn, − 20% in summer) and earthworms (anecic—two Lumbricus terrestris , endogeic—four Allolobophora chlorotica and both together within 10 cm diameter tubes) on plant biomass and stoichiometry in two land-use types (intensively used meadow and conventional farming). We found little evidence for earthworm effects on aboveground biomass. However, future climate increased above- (+40.9%) and belowground biomass (+44.7%) of grass communities, which was mainly driven by production of the dominant Festulolium species during non-summer drought periods, but decreased the aboveground biomass (− 36.9%) of winter wheat. Projected climate change and earthworms interactively affected the N content and C:N ratio of grasses. Earthworms enhanced the N content (+1.2%) thereby decreasing the C:N ratio (− 4.1%) in grasses, but only under ambient climate conditions. The future climate treatment generally decreased the N content of grasses (aboveground: − 1.1%, belowground: − 0.15%) and winter wheat (− 0.14%), resulting in an increase in C:N ratio of grasses (aboveground: + 4.2%, belowground: +6.3%) and wheat (+5.9%). Our results suggest that climate change diminishes the positive effects of earthworms on plant nutrient uptakes due to soil water deficit, especially during summer drought.

Post-fire forest floor succession in a Central European temperate forest depends on organic matter input from recovering vegetation rather than on pyrogenic carbon input from fire - Veronika Jílková; Martin Adámek; Gerrit Angst; Michala Tůmová; Miloslav Devetter (Science of The Total Environment, 2023)

Earthworms as catalysts in the formation and stabilization of soil microbial necromass - Gerrit Angst; Jan Frouz; Jan Willem van Groenigen; Stefan Scheu; Ingrid Kögel‐Knabner; Nico Eisenhauer (Global Change Biology, 2022)
Microbial necromass is a central component of soil organic matter (SOM), whose management may be essential in mitigating atmospheric CO 2 concentrations and climate change. Current consensus regards the magnitude of microbial necromass production to be heavily dependent on the carbon use efficiency of microorganisms, which is strongly influenced by the quality of the organic matter inputs these organisms feed on. However, recent concepts neglect agents relevant in many soils: earthworms. We argue that the activity of earthworms accelerates the formation of microbial necromass stabilized in aggregates and organo‐mineral associations and reduces the relevance of the quality of pre‐existing organic matter in this process. Earthworms achieve this through the creation of transient hotspots (casts) characterized by elevated contents of bioavailable substrate and the efficient build‐up and quick turnover of microbial biomass, thus converting SOM not mineralized in this process into a state more resistant against external disturbances, such as climate change. Promoting the abundance of earthworms may, therefore, be considered a central component of management strategies that aim to accelerate the formation of stabilized microbial necromass in wide locations of the soil commonly not considered hotspots of microbial SOM formation.

Changes in the quality of marcescent and shed senescent leaves during the dormant season - Šárka Angst; Hana Veselá; Martin Bartuška; Veronika Jílková; Jan Frouz; Gerrit Angst (Plant and Soil, 2022)

Tree species identity alters decomposition of understory litter and associated microbial communities: a case study - Šárka Angst; Lenka Harantová; Petr Baldrian; Gerrit Angst; Tomáš Cajthaml; Petra Straková; Jan Blahut; Hana Veselá; Jan Frouz (Biology and Fertility of Soils, 2019)

Soil organic carbon stability in forests: Distinct effects of tree species identity and traits - Gerrit Angst; Kevin E. Mueller; David M. Eissenstat; Susan Trumbore; Katherine H. Freeman; Sarah E. Hobbie; Jon Chorover; Jacek Oleksyn; Peter B. Reich; Carsten W. Mueller (Global Change Biology, 2019)
Rising atmospheric CO 2 concentrations have increased interest in the potential for forest ecosystems and soils to act as carbon (C) sinks. While soil organic C contents often vary with tree species identity, little is known about if, and how, tree species influence the stability of C in soil. Using a 40 year old common garden experiment with replicated plots of eleven temperate tree species, we investigated relationships between soil organic matter (SOM) stability in mineral soils and 17 ecological factors (including tree tissue chemistry, magnitude of organic matter inputs to the soil and their turnover, microbial community descriptors, and soil physicochemical properties). We measured five SOM stability indices, including heterotrophic respiration, C in aggregate occluded particulate organic matter (POM) and mineral associated SOM, and bulk SOM δ 15 N and ∆ 14 C. The stability of SOM varied substantially among tree species, and this variability was independent of the amount of organic C in soils. Thus, when considering forest soils as C sinks, the stability of C stocks must be considered in addition to their size. Further, our results suggest tree species regulate soil C stability via the composition of their tissues, especially roots. Stability of SOM appeared to be greater (as indicated by higher δ 15 N and reduced respiration) beneath species with higher concentrations of nitrogen and lower amounts of acid insoluble compounds in their roots, while SOM stability appeared to be lower (as indicated by higher respiration and lower proportions of C in aggregate occluded POM) beneath species with higher tissue calcium contents. The proportion of C in mineral associated SOM and bulk soil ∆ 14 C, though, were negligibly dependent on tree species traits, likely reflecting an insensitivity of some SOM pools to decadal scale shifts in ecological factors. Strategies aiming to increase soil C stocks may thus focus on particulate C pools, which can more easily be manipulated and are most sensitive to climate change.

Retention of dead standing plant biomass (marcescence) increases subsequent litter decomposition in the soil organic layer - Šárka Angst; Tomáš Cajthaml; Gerrit Angst; Hana Šimáčková; Jiří Brus; Jan Frouz (Plant and Soil, 2017)